Consecutive Immunohistochemical Staining on a Single Slide is Effective in Confirming Melanocytic Derivation. Issue 9 (October 2020) - Campbell, Katelynn K.; Gardner, Jerad M.; Hall, Kim; Osborne, Amanda; Shalin, Sara C.
Abstract : Background: Metastatic melanoma in sentinel lymph nodes is often elusive to detect with morphology alone. Per American Joint Committee on Cancer staging guidelines, a single atypical melanocyte in lymph node qualifies as metastasis, whether identified by morphology or immunohistochemistry, but single cell staining must be convincing. We propose that the use of a second immunohistochemical run performed on a single slide will allow for more confident diagnosis of micrometastases. Materials and Methods: We designed a technical study to determine whether a second antibody application on previously stained slides can successfully detect the same population of cells. Melanocytic neoplasms were stained with SOX-10 using Ventana Benchmark Ultra stainers, coverslipped, and examined, followed by coverslip removal and application of MART-1 (Ventana A103). The order of antibody application and chromagen detection kit (AP-RED vs. DAB) was reversed to establish reliability and robustness of the protocol. Results: All melanocytes marked with SOX-10 and MART-1, and produced a range of staining quality that varied based on order of stain application and chromagen kit were used. The optimal combination was red MART-1 applied first followed by brown SOX-10 applied second. Conclusions: Consecutive staining of melanocytes with SOX-10 and MART-1 may improve diagnostic confidence of melanocyte identification, particularly in detection of single cell, micrometastases in sentinel lymph nodes or in situations where dual immunohistochemical stains may be unavailable.